Spiritual Transformation and Mental Fortification: An Analysis of Tariqat Al-Rifa'iyah's Contribution to the Psychological Development of Da'i from Zuhud to Shaja'ah - Fajar, Dadang Ahmad; Saepulrohim, Asep (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2025)
Tariqat al-Rifa'iyah is a mu'tabarah tariqat (connected to the Prophet Muhammad), which is spread throughout the world, including in Indonesia. The development of Thariqat al-Rifa'iyah teachings is growing rapidly in various provinces. The interesting thing to research in thariqat al-Rifa'iyah is the process of fostering the saliknya towards an attitude of shaja'ah (courageous for defending the truth). The purpose of this research is to gain clarity about the movement of thariqat al-Rifa'iyah as a zuhud thariqat, in fostering shaja'ah. Tariqat al-Rifa'iyah succeeded in contributing to the cultivation of the soul of shaja'ah. For this reason, researchers prove its success which has differences with other coaching patterns. This research uses qualitative method to explain the role of Tariqat al-Rifa'iyah in coaching towards shaja'ah attitude. The description includes the results of interviews with several practitioners of thariqat Rifa'iyah in Cianjur and Banten. Researchers use the theory of Sufism in conducting research. Because the connection of human soul development in Islamic teachings is carried out by Sufis and benefits as an addition to the scientific treasures of Islamic psychotherapy. The results obtained are that thariqat al-Rifa'iyah is a zuhud thariqat that is directed to contribute courage through special spiritual development. This coaching can apparently be included in the thariqat-based Sufistic therapy method.